A Meta-Analysis of the Price and Income Elasticities of Food Demand - Fabienne Femenia (German Journal of Agricultural Economics (GJAE), 2019)
Food demand elasticities are crucial parameters in the calibration of simulation models used to assess the impacts of political reforms or to analyse long-term projections, notably in agricultural sectors. Numerous estimates of these parameters are now available in the economic literature. The main objectives of this work are twofold: we seek first to identify general patterns characterizing the
Keywords: 330